Metaverse in Education: A Survey-Based Investigation of Collaborative Learning and Immersive Experiences - Youssef, Enaam; Al Malak, Mahra; Bayoumy, Mohamed (Emerging Science Journal, 2024)
This study employed a survey-based approach supported by the Community of Inquiry (CoI) framework to investigate the effect of the Metaverse on education, with a special focus on collaborative learning, opportunities, and immersive experiences. Data collected from 337 university students provided insights regarding the perceptions, opportunities, and experiences linked with metaverse technologies in educational settings. Study findings remained supportive towards the preliminary hypotheses. The first hypothesis confirmed a significant effect on Collaborative Learning. The second hypothesis also indicated a significant effect of metaverse technology on Learning Opportunities. Finally, the third hypothesis, focusing on Immersive Experiences, also remained significant. Overall, the respondents agreed that the Metaverse is a positive addition, improving their learning experiences and motivating them to engage in learning activities. Finally, the research discussed implications, limitations, and recommendations for future studies. Doi: 10.28991/ESJ-2024-SIED1-022 Full Text: PDF